2008
DOI: 10.1021/es7028284
|View full text |Cite
|
Sign up to set email alerts
|

Bangladesh and Vietnam: Different Groundwater Compositions Require Different Approaches to Arsenic Mitigation

Abstract: In the large cities, groundwater is treated in central water treatment plants. In rural areas, the water supply is highly decentralized, and more than 12 million tubewells provide THIS IMAGE AND TOC GRAPHIC BY SAMUEL LUZI, EAWAG

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 23 publications
4
90
0
Order By: Relevance
“…These in situ formed iron surface sites could also contribute to As adsorption (Maiti et al 2013). A similar observation was also reported in filtration experiments for groundwater As removal (Hug et al 2008;Leupin et al 2005).…”
Section: Field Column Resultssupporting
confidence: 73%
“…These in situ formed iron surface sites could also contribute to As adsorption (Maiti et al 2013). A similar observation was also reported in filtration experiments for groundwater As removal (Hug et al 2008;Leupin et al 2005).…”
Section: Field Column Resultssupporting
confidence: 73%
“…In order to emphasize the applicability of our new MGNC adsorbent to remove arsenate from the natural system, As(V)-contaminated groundwater was artificially prepared from distilled water spiked with arsenate and other commonly found cations and anions, as previously described in the literatures (Table 3), 19,20 and the remediation process was tested. One liter of artificial contaminated groundwater spiked with arsenate (0.6 mg/L) along with the various cations and anions was treated with 1.0 g of 100 nm MGNCs in the Erlenmeyer flask, as shown in Graphical Abstract.…”
Section: Resultsmentioning
confidence: 99%
“…But in this study, there was significantly a positive relationship between the sand and sedimentary as content while a negative correlation was found between TOM and mud with Arsenic (p<0.01) ( Table 2) and may be related to geology. The geology plays a crucial role in arsenic mitigation [27]. Sediments typically contain only modest levels of arsenic and the cause and timing of arsenic mobilization from these sediments remain unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Sediments typically contain only modest levels of arsenic and the cause and timing of arsenic mobilization from these sediments remain unclear. Vulnerable areas for arsenic contamination are typically young Quaternary deltaic and alluvial sediments [5], with a typically high content of organic matter [27]. Moreover, Berg et al (2007) found a correlation with sediment-bound iron.…”
Section: Resultsmentioning
confidence: 99%